(3GOGQI GdeUGQa GdGSdGejI (B:s (3eONd MOjK (B/s - (3YQjbGJ, MQHj eMeOs; (3Ybd, SYjO LeYI s ((3YeGf(B: s (3OGQ hGFd(B, s, 2010)
(3GdfXGe GdGbJUGOj aj GdESdGe , GdLgGR GdeUQaj h GdeUGQa GdGSdGejI , eaGgje CSGSjI aj GdeUGQa GdGSdGejI , COhGJ GdJehjd GdGSdGejI GdeVGQHI h GdeTGQcI , GdeQGHMI h GdGLGQI , GdSde h GdGSJUfGY h GdbQhV GdMSfI , GdNOeGJ GdeUQajI GdGSdGejI h GdJfXje GdGOGQj ddeUQa GdGSdGej h GdQbGjI Ydi GdfTGW GdeUQaj GdGSdGej , GOGQI eNGWQ GdeUGQa GdGSdGejI eY hLhO CSFdI ddefGbTI aj fgGjI cd aUd (B.s
(3eQGLY U(B.331 (3; edGMb U(B.335s
Keywords: (3GdEOGQIs; (3GdeUGQa GdESdGejIs